(untitled) (Andamios, Revista de Investigación Social, 2025)
This paper discusses gesture as a gender marker in oral communication. It considers two principles: the fact that oral communication acts consist of more than linguistic utterances; and the fact that the gender of these acts must be determined by considering performance and context elements. After analyzing a series of examples on how gesture characterizes different oral genres, the article proposes ideas for using classifications of nonverbal communication in order to perform complementary analyses of verbal content.